The Prognostic and Therapeutic Potential of LRIG3 and Soluble LRIG3 in Glioblastoma - Cheng, Fangling; Zhang, Po; Xiao, Qungen; Li, Youwei; Dong, Minhai; Wang, Heping; Kuang, Dong; He, Yue; Duan, Qiuhong; Mao, Feng; Wang, Baofeng; Guo, Dongsheng (Frontiers in Oncology, 2019)
Glioblastoma is a highly lethal type of primary brain tumor that exhibits unrestricted growth and aggressive invasion capabilities, leading to a dismal prognosis despite a multitude of therapies. Multiple alterations in the expression level of genes and/or proteins have been identified in glioblastomas, including the activation of oncogenes and/or silencing of tumor-suppressor genes. Nevertheless, there are still no effective targeted therapies associated with these changes. In this study, we investigated the expression of human leucine-rich repeats and immunoglobulin-like domains protein 3 (LRIG3) in human glioma specimens through immunohistochemical analysis. The results showed that LRIG3 was weakly expressed in high-grade gliomas (WHO [World Health Organization] grades III and IV) compared with that in low-grade gliomas (WHO grade II). Survival analysis of these patients with glioma indicated that LRIG3 is an important prognostic marker for better survival. Moreover, we confirmed the existence of soluble ectodomain of LRIG3 (sLRIG3) in the cell culture supernatant, serum, and in tumor cystic fluid of patients with glioma. Molecular mechanistic investigation demonstrated that both LRIG3 and sLRIG3 inhibit the growth and invasion capabilities of GL15, U87, and PriGBM cells and tumor xenografts in nude mice through regulating the MET/phosphatidylinositol 3-kinase/Akt signaling pathway. Enzyme-linked immunosorbent assay confirmed the positive correlation between serum sLRIG3 protein levels and overall survival time in patients with high-grade gliomas. Taken together, our data for the first time demonstrate the existence of sLRIG3 and that both LRIG3 and sLRIG3 are potent tumor suppressors, which could be used as prognostic markers for better overall survival and therapeutic agents for glioblastoma.